An improved Cuckoo search localization algorithm for UWB sensor networks - Qin, Xiaofeng; Xia, Bin; Ding, Tian; Zhao, Lei (Wireless networks, 2021)
Conventional Cuckoo search (CS) localization method can obtain good positioning results that are highly accurate and robust. However, its positioning performance is constrained by the limited distance information available between the unknown node and the anchor node. In order to further enhance the positioning accuracy of the CS method, an improved CS localization algorithm is proposed that can take advantage of all of the distance information available. In the positioning process, an objective function which contains the distance information among the unknown nodes is given. Firstly, we use this distance information between the anchor node and the unknown node to determine an initial position through the conventional CS method. Then, based on the initial position, all of the distance information available is used to compute a more precise position. The simulation results demonstrate that the proposed algorithm can enhance the positioning accuracy in comparison with the conventional CS algorithm.